Freedom of speech issues in Peach v Toohey and a hypothetical variant of that case - Patrick Keyzer (Asia Pacific Network, 2004)
The purpose of this article is to consider the tensions within Australian free speech jurisprudence based on a hypothetical variant of the facts of the decision of the Supreme Court of the Northen Territory in Peach v Toohey. In particular, this article briefly explores the competing legal interests  that operate when journalists seek access to restricted areas, in this case aborginal land, in the course of an investigation. After considering the case and the issues it raises the author develops a hypothetical that draws out some of the deeper tensions in this area of the law. The article concludes with proposals for new apporoaches to the test developed by the High Court of Australia in Lange v Australian Broadcasting Corporation for the balancing of freedom to discuss political and governmental affairs—including the public right to know — against other legitimate objectives such as the maintence of property rights and the privacy interests that can be associated with propety rights.